On a Weak Solution of an Equation for an Evolution Flow with Interaction - Karlikova, M. P. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We prove that a stochastic differential equation for an evolution flow with interaction whose coefficients do not satisfy the global Lipschitz condition has a weak solution.